The use of motivational interviews by nurses to promote health behaviors in adolescents: developing a search strategy for this review - Cardoso, Daniela Filipa Batista (2016)
Introduction: The developmental changes during adolescence may affect subsequent risk for diseases and health-related behaviors. Motivational Interview (MI) may be taken as an essential tool in the provision of nursing care to adolescents, being itself a workspace with possible therapeutic effects. At this context, it is important to examine and map the use of MI by nurses in their clinical practice with adolescents to promote health behaviors. Objectives: A scoping review has been undertaking to find out what is the current extent of the use of nurse-led MI; which adolescents were included; in which contexts nurses use MI; which MI techniques/strategies are used and what outcomes have been reported. The first task was to develop a search strategy to identify relevant studies for this review. It is described here the experience in constructing the search strategy review. Methodology: This scoping review will be informed by JBI methodology. An initial search of MEDLINE and CINAHL was undertaken. An analysis of the text words contained in the title and abstract, and of the index terms used to describe the searched articles were retrieved and these were then used to construct a search strategy for use in Medline and Cinahl. Results: Analysis of the text words and the index terms generated 19 keywords: It was identified 5 synonyms for "Adolescents", 12 for "MI" and 2 for "nurse". A new research formula was designed using the text words identified. Adolescen*[Title/Abstract]) OR Younger*[Title/Abstract]) OR Youth*[Title/Abstract]) OR Teen*[Title/Abstract]) OR Adolescent[MeSH Terms])) AND (((((((((((("Motivational interview"[Title/Abstract]) OR "Motivational intervention"[Title/Abstract]) OR "Motivational interviews"[Title/Abstract]) OR "Motivational interventions"[Title/Abstract]) OR "motivational interviewing"[Title/Abstract]) OR "motivational counseling"[Title/Abstract]) OR "motivational support"[Title/Abstract]) OR "Motivational enhancement"[Title/Abstract]) OR "Brief intervention"[Title/Abstract]) OR "Brief interventions"[Title/Abstract]) OR Motivational Interviewing[MeSH Terms]) OR Directive Counseling[MeSH Terms])) AND ((nurs*[Text Word]) OR Nurses[MeSH Terms]). Limiters - Language: English, Portuguese, Spanish. In MEDLINE this research formula generated 125 results. Other 16 databases referenced at the protocol will be searched to identify additional studies. Articles identified from the final search will be assessed for relevance to the review, based on information provided in the title and abstract. The full article will be retrieved for all studies that meet the inclusion criteria of the review. Conclusions: It was presented here the initial results of this search. Next steps of this study will be to develop and refine the search strategy for use in other databases. It is expected that findings from this Scoping Review provide needed information to nurses related to the use of MI to promote health behaviors in adolescents and inform opportunities for future development in nursing practice.